EFFECT OF STEEPING SOLUTION ON THE QUALITY OF BUTTON MUSHROOMS (A. BISPORUS) PRESERVED UNDER AMBIENT CONDITIONS - GUPTA PRERNA,; BHAT ANJU,,; CHAUHAN HARMEET,; MALIK ANISA,; AHMED NASEER, (The Bioscan, 2015)
Steeping of the mushrooms was done with a purpose to enhance the shelf-life and various quality changes viz., pH, colour, microbial flora and antioxidant potential were studied for up to a period of 80 days. The pH of the solutions was maintained below 4.5 that helped in the inactivation of polyphenoloxidase enzyme and in lower- ing microbial growth. A gradual decrease in pH, antioxidant potential, colour and all the sensory parameters was observed whereas an increase in the growth of microbes was observed during storage. Sensory evaluation of the mushrooms was done using hedonic scale and of all the treatments, T3 was observed to be the best treatment on the basis of sensory and physico- chemical analysis.